The relationship between medical staff burnout and subjective wellbeing: the chain mediating role of psychological capital and perceived social support - Fan, Jia; Chang, Yuyang; Li, Li; Jiang, Nan; Qu, Zhifei; Zhang, Jiaxin; Li, Meihua; Liang, Bing; Qu, Danhua (Frontiers in Public Health, 2024)
Background Medical staff play a crucial role in delivering healthcare services, especially during epidemics of infectious diseases such as coronavirus disease 2019 (COVID-19). However, there is a growing issue of burnout and low wellbeing among this group. While it is widely recognized that burnout has a negative impact on subjective wellbeing, the exact relationship between the two is not yet completely understood. The purpose of this study is to explore the chain mediating role of psychological capital and perceived social support between burnout and subjective wellbeing among medical staff. Methods Using the convenient sampling method, 604 medical staff were selected for a cross-sectional study. All participants completed a self-report questionnaire that collected demographic information, as well as data from the Maslach Burnout Inventory-Human Services Survey, General Wellbeing Schedule, Psychological Capital Questionnaire, and Perceived Social Support Scale. SPSS 27.0 and SPSS PROCESS macro were used for data analysis. Results There was a significant correlation between burnout, psychological capital, perceived social support, and subjective wellbeing (p < 0.01). Burnout not only has a direct negative impact on the subjective wellbeing of medical staff (effect: −0.2045; Bootstrap 95%CI: −0.2506, −0.1583), but also exerts an indirect influence on subjective wellbeing through three pathways: the independent mediating effect of psychological capital (effect: −0.0481; Bootstrap 95%CI: −0.0876, −0.0109), the independent mediating effect of perceived social support (effect: −0.0092; Bootstrap 95%CI: −0.0203, −0.0003), and the chained mediating effect of psychological capital and perceived social support (effect: −0.0092; Bootstrap 95%CI: −0.0183, −0.0019). Conclusion High burnout in medical staff can impair the level of psychological capital, leading to diminished perceived social support and ultimately reduced subjective wellbeing. The findings of this study contribute to understanding the potential pathways between burnout and subjective wellbeing and provide preliminary data support for developing strategies to improve the mental health of medical staff.